Вы находитесь на странице: 1из 164

τ

τ

τ

τ

τ

v (M, n) , Γ : Γ = (v,M, n) , Γ f (r, Γ, t) , dV r. Γ Γ + dΓ dV t :

dN = f (r, Γ, t) dΓdV.

2 /2I T. H 2 , HD, D 2 .

r, (r, Γ) t. n (r, t) = dΓf ; r V = n dΓfv;

ε = n dΓf mv 2 + ε in ε in

= dΓf mv 2 + ε in v; Π ik = dΓfmv i v k .

Γ, f Γ

q

1

1

2

2

V

N Γ ,

Γ N Γ = dV f (r, Γ, t) . Γ V f v Γ Γ V

N Γ

∂t

N Γ

∂t

=

t V dV f = dSfv V dV f

∂t

st

;

Γ V, Γ

dSfv = V dV ∇ · (f v) ,

∂f

∂t

+ ∇ · (fv) = f ∂t

st

.

v r v

· (f v) = vf.

f st Γ

Γ Γ 1 , w (ΓΓ 1 Γ Γ 1 ) Γ Γ 1 .

∂t

∂f

∂t

st =

Γ 1 ,Γ ,Γ

1

wff 1

Γ 1 ,Γ ,Γ

1

w f f 1 .

f

f

f

f

w

w

(r, Γ, t) = f;

(r,

(r, Γ 1 , t) = f 1 ;

r, Γ

(ΓΓ 1 Γ Γ 1 ) = w;

Γ 1 ΓΓ 1 ) = w .

, t = f

Γ , t) = f ;

1

1 ;

Γ Γ f Γ 1 f 1 Γ Γ 1 Γ Γ 1 w (ΓΓ 1 Γ Γ 1 ) ff 1 Γ 1 , Γ , Γ 1 Γ

Γ Γ

Γ

dΓ d 3 v d 3 M ,

n

n f (r, Γ, t)

∂ f

∂t

+ (v) f = dΓ 1 dΓ dΓ 1 wff 1 w f f 1 = I st ,

I st Γ

m= F ext

n

M M

∂f

v +

˙

∂f

∂ f

∂t

+ (v) f +

∂f

v +

˙

M

M ∂f = I st .

E

∂ f(E)

∂t

+ (v) f (E) + f(E) +

v

M ∂f(E)

˙

M

=

∂ f(E)

∂E

E

∂t

˙

+ (v) E + E + M

v

M

∂E

∂ f(E)

∂E

dE

dt ,

dN

dt

=

N 1 Qdσ.

Q N 1 N 1 f 1 dΓ 1 Γ 1 Γ 1 + dΓ 1 , Q gf Γ v Γ 1 v 1

g

= |v v 1 | ,

dN

dt = gff 1 dΓ 1 ;

= ΓΓ 1 Γ Γ 1 .

dN

dt

= wff 1 dΓ 1 dΓ dΓ 1 , w = w ΓΓ 1 Γ Γ 1 .

wdΓ dΓ 1 = gdσ,

I st = dΓ 1 gdσff 1 g f f 1 .

v

+ v 1 = v +v

1

v 2 +v 2 = v 2 +v 2

1

1

.

G =

g = v v 1 g = v v 1 .

1 2 (v + v 1 ) G = 2 (v +v 1 )

1

G

=

G

g 2 = g 2 .

= dσ,

I st =

dΓ 1 gdσ ff 1 f f 1 .

r 0 10 8 r 1 10 6 n 1/3 n = 2.7 · 10 19 3

r 2 10 5 r 3 n (r, t) V (r, t) T (r, t)

v T m 1/2 10 5 τ 0 r T 10 13 τ 2 r T 10 10 τ 3 r T

r

r 0 3 10 5 ,

T

0

v

2

v

3

v

3

0

r

1

r 3 r 2 , τ 3 τ 2 . n (r, t) V (r, t) T (r, t) Γ

I st I es = f

dΓ 1 gdσ f 1 = f τ .

τ 1 Γ

g

v T 10 5

=

σ tot a 2 10 14 2 ;

dΓ 1 f 1

n 10 19 3 .

σ tot a

τ 1 v T σ tot n 10 10 1 .

τ 10 10 τ 2

c V T, c V T U 0 (r 0 /r 1 ) 3 , r 0 r 1

U 0 (r 0 /r 1 ) 3 c V T.

U 0 U 0 T c , T c T < T c ,

r 0 r 1 .

W. τ 2 r 2

τ 0 r 0

τ 0 τ 2 ,

r 0 r 2 .

τ 0 r 0 . f r 0 r 3 .

r 0 r 1

τ 0 τ 3 ,

r 0 r 3 .

w ΓΓ 1 Γ Γ 1 dΓ dΓ 1 = w

Γ Γ 1 ΓΓ 1 dΓ dΓ 1 ,

wdΓ dΓ 1 = w dΓ dΓ 1 .

Γ Γ 1 Γ Γ 1 , Γ Γ 1 , Γ Γ 1 . S, SS + = 1.

S in S

nk =

+

n n

S in S

kn = δ ik .

i = k

n

|S in | 2 = 1.

|S in | 2 n i, n i S + S = 1,

S

+

in S ni =

n n

|S ni | 2 = 1.

i n

|S ii | 2 i

|S in | 2 = |S ni | 2 .

n

=i

n

=i

w

I st = dΓ 1 dΓ dΓ 1

w ff 1 f f 1 .

dΓ 1 dΓ dΓ 1 wf f 1 = dΓ 1 ff 1 dΓ dΓ 1 w =

= dΓ 1 ff 1 dΓ dΓ 1 w = dΓ 1 dΓ dΓ 1 w f

f 1 .

f = f (0) = Ce E(Γ) ;

T

C

= C (r, t);

T = T (r, t) .

ff 1 f f 1 = C 2 e

E+E 1

T

e

E +E

1

T

= 0.

w. E + E 1 = E + E 1 , I st f (0) = 0.

A = A (Γ)

dΓI st A (Γ) = d 4 ΓA (Γ) wff 1 w f f

1 .

d 4 Γ = dΓdΓ 1 dΓ dΓ 1 . Γ ←→ Γ 1 . A (Γ) A 1 ) , w w

dΓI st A (Γ) = 1 2

d 4 Γ (A + A 1 ) wf f 1 (A + A 1 ) w f f

1

.

Γ ←→ Γ ,

Γ 1 ←→ Γ

1

.

A A , A 1 A 1 , f f ,

f 1 f

1

,

w w .

dΓI st A (Γ) = 1

2 d 4 Γ A + A 1 A A 1 w f f .

1

I st Γ dΓI st A (Γ) dΓfA (Γ) dΓI st n = dΓf; dΓI st mv nmV = dΓfmv; dΓI st E

¯

¯

E = dΓf E E

dΓI st = 0;

dΓI st mv = 0;

dΓI st E = 0.

w

S = dV dΓf Γ ln f Γ = dV s,

e

s

dS

dt

= dV dΓ t f Γ ln f Γ = dV dΓ f Γ ln f Γ dΓ f Γ =

e

∂t

e

∂t

dV dΓ f Γ ln f Γ dΓ f Γ = dV dΓ f Γ ln f Γ .

∂t

e

∂t

∂t

∂f Γ

∂t

= f r Γ

f p Γ I st .

dV dΓln f Γ f r Γ

= dΓ dV r f Γ ln f Γ

e

.

s˙

=

=

e

dΓ f Γ ln f Γ dΓ f Γ

∂t

∂t

1 2 d 4 Γf f 1 w ln f ff f 1

1

.

= dΓI st ln f Γ =

0 = 2

1

dΓI st · 1 =

1

2

s˙ =

1

2

d 4 Γw ff 1 1

d 4 Γw f f 1 f f 1 .

f

f 1

ff

1

+

f f 1

ff

1

ln f ff f 1

1

.

y = x ln x + 1 x. x ln x = 0, x = 1 y min = y (1) = 0. y

x = f f 1 1 ,

ff

s˙ = dΓI st ln f Γ 0 1 3 w,

r 1 , r 2 , r 1 , r 2 |r 1 r 2 |

U =

0

.

F = −∇U ,

∂f

∂t

+ (v) f + F p ∂f = I st .

t S

dV dΓ f ∂t ln f

=

=

dV dΓ t f ln f =

e

dV dΓ

(v) f + F p ∂f + I st ln f.

f = 0

dV dΓ ln f (v) f = dV dΓv

f

f

f

=

= dV dΓvf = dV dΓdiv (vf ) = 0,

dV dΓ ln f p (Ff) = dV dΓF p = dV dΓdiv p (Ff) = 0.

∂f

t S = dV dΓI st ln f.

wdΓ dΓ 1 = w dΓ dΓ

1

w w . w = w .

m¨r = F t → −t.

w ΓΓ 1 Γ Γ 1 = w Γ T Γ T Γ T Γ T ,

1

1

Γ = (v, M) , Γ T = (v, M) . Γ = (v, M) , Γ I = (v, M) .

= w T .

w

w ΓΓ 1 Γ Γ 1 = w Γ I Γ I Γ I Γ I .

1

1

w = w T w = w I w = w TI ,

w

ΓΓ 1 Γ Γ

1 = w Γ TI Γ TI

1

Γ TI Γ TI

1

,

Γ TI = (+v, M)

w vv 1 v v 1 = w v v 1

vv 1 .

w = w

γ γ

w Γγ Γ γ = w Γ T γ T Γ T γ T .

γ

ρ γ = e

FE γ

T

.

Γ Γ

w Γ Γ = ρ γ w Γγ Γ γ .

γγ

w Γ Γ = ρ γ w Γ T γ T Γ T γ T .

γγ

E γ = E γ T , ρ γ = ρ γ T .

γ γ

γ T γ T .

w Γ Γ =

γ T γ T

ρ γ T w Γ T γ T Γ T γ T .

ρ γ T =

e

w Γ Γ = e

FE ( γ T )

T

= e

E ( Γ T ) E ( Γ T )

T

FE ( γ T )

E ( Γ T ) E ( Γ T )

T

e

T

.

γ T γ T

ρ γ T w Γ T γ T Γ T γ T .

w Γ Γ = e

E ( Γ T ) E ( Γ T )

T

w Γ T Γ T .

n(r, t), V(r, t),

¯

T (r, t) A,

n A (r, t) =

¯

dΓf (r, Γ, t) A (Γ) .

Γ :

t dΓf + dΓ(v) f = dΓI st .

dΓf = n(r, t)

dΓ(v) f = dΓvf = (nV) ,

V

dΓI st = 0.

∂n

∂t

+ α (V α n) = 0, n ∂t + div (nV) = 0.

A (Γ) Γ :

t dΓfA + dΓA (v) f = dΓI st A.

dΓfA = n

¯

A.

dΓA (v) f = dΓAvf,

v A u = v V

dΓfAv = dΓfA (u + V) = V dΓfA + dΓfAu =

¯

= n AV+ dΓfAu.

A

∂t n

A + n AV+ dΓ fAu = dΓI st A.

¯

¯

A t n + n

n

¯

∂t

A ¯ + A(nV)+n VA =

¯

¯

A def

¯

=

n

d

dt

¯

A.

∂t

A + V

¯

A

¯

A :

n

d

dt

A ¯ + dΓfAu = dΓI st A.

¯

A

A

¯

n A

A n ,

¯

t dΓfA + V dΓfA + dΓfAu = dΓI st A.

A (Γ) = mv i

d

nm dt V i + k dΓ fmv i u k = 0

dΓ fmv i u k = dΓ fm (V i + u i )